Persistent mathematical errors when entering initial teacher math training: the linearity case - Aguerrea, Maitere (2022)
The objective of this research was to identify persistent errors of mathematical concepts and procedures, in particular, the incorrect application of the linearity concept, as well as implement learning situations to address errors of linearity by designing learning tasks in the context of modeling and the use of mathematical software. The study was applied to 42 students in the mathematics education program, during the 2019-2020 period. Research was conducted under a qualitative and longitudinal approach. Data collection began with a test upon entering the program and a second test after completing a semester of classes. Later on, collaborative workshops were implemented to address linearity errors, and a post-test was applied at the end. Upon entering the initial teacher math training, students showed a high percentage of errors, mistakenly applying linearity to roots, powers, logarithms, and trigonometry. After a semester of classes, these errors persisted. After the workshops, none of the participants made linearization errors in roots, powers and trigonometry, and only some continued applying linearity to logarithms. It was concluded that at the beginning of the program, students were still making errors in concepts and procedures that should have been overcome in school, and many of these errors are highly persistent. Using software in learning situations related to modeling would help students remedy those errors.